SCIENCE POLICY MEASURES TO INCREASE UNIVERSITY OUTPUT - van Dijk, P. Assoc. Prof. Jitse (Profese Online, 2013)
We explored what can be done with more efficient use of the resources and opportunities we already have such that we produce more output and more high quality output. We advocate measures for improving efficiency, such as focusing on certain research fields, publishing internationally, replacing monographs for PhD students and habilitation, by publishing international articles, educating researchers by establishing graduate schools, selecting young talent and finding international partners. All of these measures can be taken without external interference.
Keywords: science policy; policy measures